2000
DOI: 10.2527/2000.7882215x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of feed intake fluctuation and frequency of feeding on nutrient digestion, digesta kinetics, and ruminal fermentation profiles in limit-fed steers.

Abstract: Nine crossbred beef steers (344 +/- 26 kg) fitted with ruminal cannulas were used in a randomized complete block design to evaluate the effects of feeding frequency and feed intake fluctuation on total tract digestion, digesta kinetics, and ruminal fermentation profiles in limit-fed steers. In Period 1, steers were allotted randomly to one of four dietary treatments: 1) feed offered once daily at 0800; 2) feed offered once daily at 0800 with a 10% fluctuation in day-to-day feed intake; 3) feed offered twice da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 15 publications
2
28
1
3
Order By: Relevance
“…There are no other reports of daily DMI variation in lambs treated with β-AA; although, in studies carried out separately in feedlot steers, Abney et al (2007) and Montgomery et al (2009a) observed a significant increase in daily DMI variation in animals treated with RH and ZH, respectively; whereas in both studies, and in concurrence with present study, greater day-to-day DMI variation from β-AA treatment did not decreases animal performance. It seems that a greater DMI variation is needed to alter performance, since literature reports indicate that 10% (Schwartzkopf-Genswein et al, 2004;Soto-Navarro et al, 2000) or 20% (Zinn, 1994) daily intake variation did not affect significantly growth performance.…”
Section: Resultsmentioning
confidence: 99%
“…There are no other reports of daily DMI variation in lambs treated with β-AA; although, in studies carried out separately in feedlot steers, Abney et al (2007) and Montgomery et al (2009a) observed a significant increase in daily DMI variation in animals treated with RH and ZH, respectively; whereas in both studies, and in concurrence with present study, greater day-to-day DMI variation from β-AA treatment did not decreases animal performance. It seems that a greater DMI variation is needed to alter performance, since literature reports indicate that 10% (Schwartzkopf-Genswein et al, 2004;Soto-Navarro et al, 2000) or 20% (Zinn, 1994) daily intake variation did not affect significantly growth performance.…”
Section: Resultsmentioning
confidence: 99%
“…However, previous studies suggest that prefeeding VFA concentrations are similar between diets (41,48) and individuals (53) and are their lowest before feeding (11), representing a suitable baseline indicator (28). Moreover, longer periods of adaptation lead to more stable rumen environments and fermentation characteristics (29,50,53).…”
Section: Discussionmentioning
confidence: 98%
“…The most active microbes may be suppressed in muskoxen during winter if ruminal conditions of pH, SCFA, and osmolality become more variable because of changes in feeding frequency, absorption, and thermoregulation. Less frequent feeding in muskoxen during winter (Forchhammer 1995) may increase variation in ruminal pH and SCFA, as reported for domestic ruminants (Kaufmann et al 1980;Soto-Navarro et al 2000). Muskoxen may also reduce the effort of regulating ruminal conditions during winter because the endogenous heat increment after consumption of a standard meal declines between summer and winter; that is, muskoxen spend less energy on processing a meal in winter than in summer (Lawler and White 2003).…”
Section: Consequences Of Hypophagiamentioning
confidence: 91%